2017
DOI: 10.5194/npg-24-203-2017
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Wave analysis methods for space plasma experiment

Abstract: Abstract. A review of analysis methods is given on quasimonochromatic waves, turbulent fluctuations, and wavewave and wave-particle interactions for single-spacecraft data in situ in near-Earth space and interplanetary space, in particular using magnetic field and electric field data. Energy spectra for different components of the fluctuating fields, minimum variance analysis, propagation and polarization properties of electromagnetic waves, wave distribution function, helicity quantities, higher-order statist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
(60 reference statements)
3
11
0
Order By: Relevance
“…Recently, Bourouaine & Perez (2018), which we call BP18 hereafter, have investigated the validity of TH near r ≃ 10R ⊙ using numerical simulations of Reflection-driven Magnetohydrodynamic (MHD) turbulence. The authors found that the Eulerian spacetime structure of the turbulence allows for the interpretation of time signals even when TH is not applicable, largely consistent with similar works (Matthaeus et al 2010;Servidio et al 2011;Narita et al 2013;Weygand et al 2013;Klein et al 2014Klein et al , 2015Matthaeus et al 2016;Narita 2017), but with a number of important differences. For instance, BP18 find that the Eulerian decorrelation in simula-1 email: sbourouaine@fit.edu tions is consistent with spectral broadening associated with pure hydrodynamic sweeping by the large-scale eddies, combined with a Doppler shift associated with Alfvénic propagation along the background magnetic field.…”
Section: Introductionsupporting
confidence: 82%
“…Recently, Bourouaine & Perez (2018), which we call BP18 hereafter, have investigated the validity of TH near r ≃ 10R ⊙ using numerical simulations of Reflection-driven Magnetohydrodynamic (MHD) turbulence. The authors found that the Eulerian spacetime structure of the turbulence allows for the interpretation of time signals even when TH is not applicable, largely consistent with similar works (Matthaeus et al 2010;Servidio et al 2011;Narita et al 2013;Weygand et al 2013;Klein et al 2014Klein et al , 2015Matthaeus et al 2016;Narita 2017), but with a number of important differences. For instance, BP18 find that the Eulerian decorrelation in simula-1 email: sbourouaine@fit.edu tions is consistent with spectral broadening associated with pure hydrodynamic sweeping by the large-scale eddies, combined with a Doppler shift associated with Alfvénic propagation along the background magnetic field.…”
Section: Introductionsupporting
confidence: 82%
“…Because of the ambiguity of the MVA to the sign, the range of values for the angle spans over [0, 180 • ]. As mentioned by, among others, Narita (2017), the minimum variance analysis fails for linearly polarized waves because the polarization plane is not uniquely determined. Therefore, all waves with an ellipticity above 0.9 are disregarded for the analysis of the minimum variance direction.…”
Section: Minimum Variance Directionmentioning
confidence: 99%
“…The degree of polarization, the wave normal angle, and the ellipticity of the waves in both events are presented in panels (d)-(g) and (k)-(n). The degree of polarization and the ellipticity are close to 1 (red), indicating that the identified waves are purely right-handed circular whistler waves (Huang et al, 2016;Narita, 2017). The direction of the wave vector k is determined by the minimum variance analysis of B (Sonnerup & Scheible, 1998) with a time window 0.2 s. The wave normal angle, defined as the angle between the propagation direction (k) and the ambient magnetic field, varies between 0 • and 50 • in both events.…”
Section: Whistler Mode Wavesmentioning
confidence: 91%
“…Whistler mode waves have been observed prior to and during the magnetotail reconnection using Cluster data (Wei et al, 2007). At the dayside magnetopause reconnection, whistler mode waves have been reported in the separatrix region from Cluster (Graham et al, 2016) and recent Magnetospheric Multiscale Mission (MMS) observations (Le Contel, Retinò, et al, 2016;Wilder et al, 2016, 2017, Yoo et al, 2018. In the magnetotail, Cluster observations show that whistler waves occur near the separatrix region and the magnetic pileup region of downstream flows (Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 98%